Leadership In Time of Crisis: The COVID-19 Pandemic in Japan and Reflections for Malaysia - Azman, Muhammad Danial; Hassan, Asmadi (WILAYAH: The International Journal of East Asian Studies, 2021)
The 2019 Coronavirus (COVID-19) outbreak was one of the most massive pandemics in history, with over 29.6 million people infected, including over 400,000 cases in Japan. This article describes the leadership tasks in a time of crisis during the different stages of Japan’s COVID-19 strategy under Shinzo Abe and Yoshihide Suga’s leadership. Our aim is to formulate lessons from Japan for Malaysia. Shallow assessments of leadership performance often accompany the deeply rooted belief in the importance of political leadership. Such reviews never arrive more quickly than in the wake of crises - dramatic disasters of COVID-19 cases and Abe’s resignation from the prime minister post. While symbolic performance is necessary (if only because it can arouse the public), it is one of the plausible avenues for the public to express their political judgements upon leadership in a time of crisis. In this article, we adopted a qualitative method of library research and highlights the many expected tasks of Japanese prime ministers to perform, and we offer a lesson for Malaysia in times of crisis